Friends or Foes, Partners or Hegemons: Examining Anti-Apartheid Struggles, and The Pattern of Nigeria-South Africa Relations, 1994-2014 - Njoku, Bright Joseph (Covenant University Journal of Politics and International Affairs, 2021)
The total liberation of Africa from the shackles of European colonialism and racial discriminatory regimes in Southern Africa, where the twin evils lasted longer became the focal of Nigeria’s Afrocentric foreign policy at independence in 1960. Thus, the Apartheid era saw Nigeria lead other independent African states in the furtherance of South African liberation struggles. With the end of Apartheid and the international isolation that accompanied it in 1994, South Africa resumed bilateral relations and international engagements with many states and organizations from which it was excluded in the apartheid years. South Africa’s entry into the Africa scene and the international arena as an emerging democratic, economic and regional superpower at a time Nigeria had suffered image-damage and declining influence following lingering military dictatorship, and internal political drawbacks, combined to alter Nigeria’s position as the continent’s sole giant and voice, albeit, momentarily. While Nigeria continued her Africa-centred Foreign Policy posture and leadership thereafter, rivalry and competition fuelled by a range of historical, political and soft issues have surfaced to shape relations between it and South Africa. Using the Hegemonic Stability Theory, this paper explores the emerging wrangling and internecine rivalry in the postapartheid era, its impact on their relations and the implication for the continent as a whole. It also examines the ruthless rights violation perpetrated against the blacks by the apartheid regime on the ground of racial superiority and Nigeria’s contribution to the efforts to dismantle it. It concludes that healthy competition and partnership between Nigeria and South Africa will undoubtedly prove equally beneficial to both, and indeed the continent at large